Estimated PCDD/F TEQ and total TEQ concentrations in the serum of 7–10 year old Finnish children - Rantakokko, Panu; Tuomisto, Jouni T.; Viluksela, Matti; Tuomisto, Jouko; Airaksinen, Riikka; Raitakari, Olli; Karvonen, Anne M.; Pekkanen, Juha; Kiviranta, Hannu (Chemosphere (Oxford), 2020)
Polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs) and polychlorinated biphenyls (PCBs) are persistent organic pollutants that have detrimental health effects. As people are exposed to them mainly through the diet, EU has set maximum food dioxin and PCBs levels. EFSA CONTAM Panel made new risk assessment in 2018 that lowered the tolerable weekly intake (TWI) from 14 pg-TEQ/kg bw/week to 2 pg-TEQ/kg bw/week. Critical effect was decreased semen count at the age of 18–19 years if serum total TEQ at the age of 9 years exceeded the No Observed Adverse Effect Level (NOAEL) of 7 pg/g lipid. However, it is largely unknown to what extent NOAEL is exceed in European boys currently. We thus measured PCBs from small volume of serum in 184 Finnish children 7–10 years of age. To estimate the TEQ levels of children from measured PCB levels, we used our existing human milk PCDD/F and PCB concentrations to create a hierarchical Bayesian regression model that was used to estimate TEQs from measured PCBs. For quality control (QC), three pooled blood samples from 18 to 20 year old males were measured for PCDD/Fs and PCBs, and estimated for TEQs. In QC samples measured and estimated TEQs agreed within 84%–106%. In our estimate for 7–10 year old children, PCDD/F TEQ exceeded NOAEL only in 0.5% and total TEQ in 2.7% of subjects. Risk management following the decreased TWI proposed by the CONTAM Panel should be carefully considered if total TEQ in children is already largely below the NOAEL. •Critical Russian study generated a NOAEL of 7 pg total TEQ/g lipid in 9 year old boys.•Nine major PCBs were measured in serum of 184 Finnish children 7–10 years of age.•Bayes model was used to estimate serum total TEQ concentrations with PCBs.•The model predicted that total TEQ was below the NOAEL in 97.3% of children.•Little health benefits are achieved with further reduction in food maximum levels.